2015
DOI: 10.3892/etm.2015.2790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histological predictive risk factors of atrial fibrillation in patients undergoing open-heart surgery

Abstract: Abstract. Postoperative atrial fibrillation (POAF) is a common complication subsequent to cardiac surgery. Various risk factors have been reported for the development of this complication; however, their precise role in POAF is unknown. In the present study, we attempted to identify clinical factors and histopathological changes in atrial tissue that may predict the development of POAF. Atrial tissue was sampled from 103 patients in sinus rhythm that had undergone open-heart surgery, including elective coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Their conclusion appears to be contrary to ours, and the difference in disease models and preoperative pathophysiological changes may contribute to the different mechanisms of POAF. Our research showed that elevated PASP was an independent predictor of POAF and was in accordance with a retrospective study that suggested that pulmonary hypertension, as evaluated by transthoracic echocardiography, was associated with an increased prevalence of POAF . The potential mechanism can be explained as 2 aspects: (1) In some patients, the simultaneously elevated PASP and PCWP may both reflect the overloading of left heart, which was mostly recognized to be responsible for the occurrence of POAF.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Their conclusion appears to be contrary to ours, and the difference in disease models and preoperative pathophysiological changes may contribute to the different mechanisms of POAF. Our research showed that elevated PASP was an independent predictor of POAF and was in accordance with a retrospective study that suggested that pulmonary hypertension, as evaluated by transthoracic echocardiography, was associated with an increased prevalence of POAF . The potential mechanism can be explained as 2 aspects: (1) In some patients, the simultaneously elevated PASP and PCWP may both reflect the overloading of left heart, which was mostly recognized to be responsible for the occurrence of POAF.…”
Section: Discussionsupporting
confidence: 88%
“…Our research showed that elevated PASP was an independent predictor of POAF and was in accordance with a retrospective study that suggested that pulmonary hypertension, as evaluated by transthoracic echocardiography, was associated with an increased prevalence of POAF. 21 The potential mechanism can be explained as 2 aspects: (1) In some patients, the simultaneously elevated PASP and PCWP may both reflect the overloading of left heart, which was mostly recognized to be responsible for the occurrence of POAF. (2) In other patients with elevated PASP but normal PCWP, the overloading of left heart may not be the main cause of POAF.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were instructed to complete a comprehensive neuropsychological battery. Global mental functioning was assessed through the Chinese version of Mini Mental State Examination (MMSE) [13], the Clinical Dementia Rating scale (CDR) and the Beijing version of Montreal Cognitive Assessment (MoCA) [14], under the supervision of a physician. The subsequent neuropsychological battery was tested in 5 cognition domains: 1) memory, tested by the Auditory Verbal Learning (AVLT-delay recall) [15]; 2) visuospatial ability and attention, tested by the Symbol Digit Modalities Test (SDMT) [16]; 3) language, tested by the Category Verbal Fluency Test [17]; 4) processing speed, tested by the Stroop Test (Stroop B-time) [18] and the Trail Making Test A (TMTa) [19] and 5) executive function, tested by the Trail Making Test B-A (TMTba) and the Stroop Test (Stroop CB-time).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the lengths of hospital stay and ICU stay were significantly higher in patients with POAF. Age was an important predictor of developing POAF after cardiac surgery (12). The mean age of the patients in the present study was 63.8 ± 9.4 years, and the patients in the POAF group were significantly older than those in the sinus rhythm group (69.2 ± 8.3 years vs. 62.1 ± 9.1 years, respectively, p < 0.01).…”
Section: Discussionmentioning
confidence: 61%